Regulation of Rat Intrapulmonary Arterial Tone by Arachidonic Acid and Prostaglandin E2 during Hypoxia - Yan, Gaoliang (Public Library of Science, 2013)
AIMS: Arachidonic acid (AA) and its metabolites, prostaglandins (PG) are known to be involved in regulation of vascular homeostasis including vascular tone and vessel wall tension, but their potential role in Hypoxic pulmonary vasoconstriction (HPV) remains unclear. In this study, we examined the effects of AA and PGE2 on the hypoxic response in isolated rat intrapulmonary arteries (IPAs). METHODS AND RESULTS: We carried out the investigation on IPAs by vessel tension measurement. Isotetrandrine (20 µM) significantly inhibited phase I, phase IIb and phase IIc of hypoxic vasoconstriction. Both indomethacin (100 µM) and NS398 attenuated KPSS-induced vessel contraction and phase I, phase IIb and phase IIc of HPV, implying that COX-2 plays a primary role in the hypoxic response of rat IPAs. PGE2 alone caused a significant vasoconstriction in isolated rat IPAs. This constriction is mediated by EP4. Blockage of EP4 by L-161982 (1 µM) significantly inhibited phase I, phase IIb and phase IIc of hypoxic vasoconstriction. However, AH6809 (3 µM), an antagonist of EP1, EP2, EP3 and DP1 receptors, exerted no effect on KPSS or hypoxia induced vessel contraction. Increase of cellular cAMP by forskolin could significantly reduce KPSS-induced vessel contraction and abolish phase I, phase II b and phase II c of HPV. CONCLUSION: Our results demonstrated a vasoconstrictive effect of PGE2 on rat IPAs and this effect is via activation of EP4. Furthermore, our results suggest that intracellular cAMP plays dual roles in regulation of vascular tone, depending on the spatial distribution of cAMP and its coupling with EP receptor and Ca(2+) channels.